2022
DOI: 10.3390/ijms23052405
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Architecture of Grain Yield-Related Traits in Sorghum and Maize

Abstract: Grain size, grain number per panicle, and grain weight are crucial determinants of yield-related traits in cereals. Understanding the genetic basis of grain yield-related traits has been the main research object and nodal in crop science. Sorghum and maize, as very close C4 crops with high photosynthetic rates, stress tolerance and large biomass characteristics, are extensively used to produce food, feed, and biofuels worldwide. In this review, we comprehensively summarize a large number of quantitative trait … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 188 publications
0
9
0
Order By: Relevance
“…NGS has accelerated work in cloning genes underlying grain yield-related features over the last two decades in sorghum 51 . Previous studies have shown that qTGW1a (Sobic.001G341700) encoding G-protein γ subunit located at the N-terminus are responsible for grain weight in sorghum 52 .…”
Section: Discussionmentioning
confidence: 99%
“…NGS has accelerated work in cloning genes underlying grain yield-related features over the last two decades in sorghum 51 . Previous studies have shown that qTGW1a (Sobic.001G341700) encoding G-protein γ subunit located at the N-terminus are responsible for grain weight in sorghum 52 .…”
Section: Discussionmentioning
confidence: 99%
“…There have been 25 patents related to the improvement of maize yield through the CRISPR-Cas editing of different target genes, accounting for 20.33% of 123 patents. Maize yield is determined by multiple genetic factors, such as effective ear number, kernel number per ear, and 100-kernel weight, as well as by environmental conditions [ 14 , 15 ]. The key genes controlling yield-related traits are, for example, ZmRLK7, ZmEREB102, ZmCEP1, UB2, UB3, ZmCO2, and GT1, and their editing can increase maize yield [ 16 , 17 , 18 ] ( Supplementary Table S1 ).…”
Section: Effective and Precise Improvement Of Agronomic Traitsmentioning
confidence: 99%
“…The domestication of cereal crops has long been focused on increasing grain yield and quality, and a series of common phenotypes have been sieved around this aspect, such as increased apical dominance, increased tillering, reduced seed shedding, increased quantity and quality, and other traits. In addition to improving yields and reducing grain losses, nutritional improvement of grain sorghum is now receiving increasing attention. Compared with other food crops, sorghum foods are rich in high-antioxidant anthocyanins, rich polyphenols, and other healthful substances, which makes health food developed from sorghum grains as raw materials popular among consumers. , Therefore, it is increasingly important to improve sorghum yields to alleviate food problems and develop multifunctional foods from grain sorghum …”
Section: Introductionmentioning
confidence: 99%